Metronome-guided training accelerates the adaptation to an aerobic training pace in swimming - Fassone, M.; Puce, L.; Biggio, M.; Avanzino, L.; Bove, M.; Bisio, A. (Frontiers in Sports and Active Living, 2025)
Swimmers often use metronomes during training, but their effectiveness in learning a new swimming pace is unclear. Adapting motor skills to new timing is complex and occurs in stages. This study investigated these stages by assessing the ability of swimmers to reproduce a learned pace without a metronome. In total, 24 participants were divided into two groups. The main group completed 4 days of training/testing and 3 follow-up days. Each training day included a 100 m front crawl trial without a metronome, followed by three 2 × 100 m training sets with metronome synchronization and a further 100 m test without the metronome. The performance measures were total 100 m time, 25 m lap times, temporal errors over 100 m (Err100) and 25 m (Err25), and the coefficient of variation of Err25 (CV). The control group followed the same protocol, but only for 2 days. Results showed that in the main group, Err100, Err25, and CV improved after the first training day and remained consistent throughout the week. Notably, Err25 and CV improvements persisted up to 10 days post-training. The control group showed no improvement after 2 days. These results suggest that metronome-guided training effectively helps swimmers adapt their pace to new motor timing, with effects lasting up to 10 days.